Preparation and characterization of carboxymethyl cellulose/poly (ethylene glycol) -rosin pentaerythritolester polymeric nanoparticles: Role of intrinsic viscosity and surface morphology - Karakus, Selcan; Ilgar, Merve; Tan, Ezgi; Kahyaoglu, Ibrahim Mizan; Tasaltin, Nevin; Albayrak, Inci; Insel, Mert Akin; Kilislioglu, Ayben (ELSEVIER, 2020)
Polymeric nanoparticles gained importance due to their excellent chemical, physical and biological properties. Herein, novel sonochemical synthesized polymeric nanoparticles were constructed based on carboxymethyl cellulose (CMC)/poly (ethylene glycol) (PEG) polymer blend matrix and rosin pentaerythritolester (RE). Determining the rheology of the novel nanostructure by using dilute solution viscometer (DSV) method was aimed in this paper. This paper was aimed at to determine on the rheology of the novel nanostructure using the dilute solution viscometer (DSV) method.The influence of the temperature, mass ratio, and salt on the intrinsic viscosity of the synthesized CMC/PEG-RE nanoparticles was investigated and its physico-chemical properties were optimized using different mathematical equations such as Huggins, Kraemer, Tanglertpaibul-Rao, Higiro and Rao. The Krigbaum-Wall parameter, Berry number and dimensionless parameter were calculated to understand the degree of miscibility and the synergistic interaction of nanostructures. The Huggins was found to be the most suitable model with the highest correlation constant (R-2: 0.94-0.99), and the intrinsic viscosity (22.2-23.4 dl/g). The surface morphology and chemical analysis of the polymeric nanoparticles were evaluated by Fourier-transform infrared spectroscopy (FTIR) and scanning transmission electron microscope (STEM). The results provided a better understanding of RE interactions in CMC/PEG polymer blends and colud be a promising nanocarrier for biomedical applications.
Keywords: Polymeric nanoparticle; Viscosity; Surface morphology; Interfacial interactions; Polymer miscibility; Rosin pentaerythritol ester; DILUTE-SOLUTION PROPERTIES; GUM; TEMPERATURE; PREDICTION; XANTHAN; Chemistry; Materials Science; Physics